PERLUASAN MAKNA HARTA BERSAMA PERSPEKTIF SOSIOLOGI HUKUM ISLAM - Hamdi, Isnadul (JURIS (Jurnal Ilmiah Syariah), 2018)
This research is based on the problems in the distribution of common property. First, the emerging of differences in the system of distributing of common property in talak raj'i and talak ba'in. Second, the occurrence of expansion in terms of income during marriage such as the existence of insurance. Third, the existence of the agreement in marriage before the joint property is shared. The result of the research shows that in the sociology perspective of Islamic law the effort to share the common property: first, in the case of divorce because the situation is still in the iddah period of talak raj'i, property should not be divided because it minimizes the possibility of reunification. Unlike the case if talak ba'in, property should be devidedd soon because it certainly will not be reunited. Second, in response to the expansion of common property such as the existence of insurance money, all Indonesian Judge agreed that all property acquired during marriage is related to Taspen Insurance, Asabri Fund, Labor Insurance, Traffic Accident Fund, Passenger Accident Fund, Life Insurance Fund, Property of Luggage, Credit that has not paid off. Third, the agreement in marriage greatly affects the distribution of common property given the existence of Article 45, 52, and 97 Compilation of Islamic Law "divorced or divorced widow respectively entitled to two joint property as long as not specified in the marriage agreement.